The Design and Performance Evaluation of a Double-three-phase Inverter - DC-Link Thermal Evaluation and Lifetime Estimation - Yodwong, Jedsada (My University, 2025)
This thesis presents the design, implementation, and experimental evaluation of a double–three–phase traction inverter based on silicon carbide (SiC) power modules for heavyduty electric vehicle applications. The work focuses on achieving high power density and robust thermal performance through co-design of the DC-link capacitor bank and laminated busbar structure. Two alternative DC-link layouts were investigated: Case I, with capacitors mounted above the busbar, and Case II, with capacitors in direct contact with the housing. A comprehensive methodology combining analytical modeling, MATLAB/Simulink simulations, and laboratory testing was employed. Open-loop SVPWM tests validated inverter functionality, while thermal performance was assessed under RMS ripple currents of 156 Arms and 300 Arms at 10 kHz under 2 thermal conditions: with and without liquid cooling. Results show that liquid cooling significantly reduces busbar temperatures (up to 67% in Case I), whereas capacitor hot-spot remain dominated by internal thermal paths, limiting improvements to 18–21%. Lifetime analysis, based on datasheet models, experimental data, and MATLAB/Simulink model, indicates that capacitor lifetime is highly sensitive to temperature. Under ideal assumptions, the lifetime at 55 ◦C ambient was estimated at 24.8 years, whereas experimentally adjusted scenarios ranged from 8.7 to 13.1 years. Liquid cooling improved lifetime by up to 50% at high ripple currents compared to the worst case, emphasizing the importance of accurate thermal modeling and integrated cooling strategies for next-generation traction inverters. The findings underscore the importance of integrated electro–thermal design for reliability in high-power SiC-based traction inverters. Future work includes closed-loop control implementation, and EMI/EMC characterization.
Keywords: SiC MOSFET, double–three–phase inverter, DC-link capacitor, laminated busbar, thermal management, lifetime estimation, electric heavy-duty vehicles.